Development of mathematics learning media using Google-sites with Teaching at The Right Level to improve problem-solving ability - Putriani Putriani; Anton Nasrullah; Vidya Ayuningtyas; Mira Marlina; Sarah Caesarani; Kewwalee Kumyai (UNION : Jurnal Ilmiah Pendidikan Matematika, 2026)
This study aimed to develop Google Sites–based mathematics learning media integrated with the Teaching at the Right Level (TaRL) approach to support tenth-grade students’ mathematical problem-solving ability on the topic of exponents. The study was motivated by the need for adaptive and interactive learning media that can accommodate students’ different ability levels. This research employed a Research and Development (R&D) method using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The participants were 30 tenth-grade students from one public senior high school in Banten, Indonesia, selected through purposive sampling for a limited trial. The developed media was evaluated based on validity, practicality, and effectiveness. Validity was assessed through media and material expert validation, practicality was measured using student response questionnaires, and effectiveness was determined based on learning mastery, improvement in problem-solving scores, paired-sample t-test, and N-Gain analysis. The results showed that the media obtained validation scores of 83% from both media and material experts, indicating that it was highly valid. Student responses reached 82.5%, indicating that the media was highly practical. The learning mastery level reached 81.6%, exceeding the predetermined effectiveness criterion of at least 80%. In addition, the average problem-solving score increased from 60% in the pre-test to 80% in the post-test, with a statistically significant difference between pre-test and post-test scores (p < 0.05). These findings suggest that Google Sites–based learning media integrated with the TaRL approach showed potential to support students’ mathematical problem-solving ability in the limited trial context. This study contributes to mathematics education by providing empirical evidence that integrating Google Sites with the Teaching at the Right Level (TaRL) approach can serve as an adaptive digital learning solution that supports differentiated instruction and enhances students' mathematical problem-solving ability.